Extraction and Fractionation Processes of Functional Components in Food Engineering (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue on the "Extraction and Fractionation Processes of Functional Components in Food Engineering" aims to bring together novel advances in the development and application of innovative processing strategies to extract, isolate, and modify food compounds to produce ingredients and foods with improved nutritional, functional, and biological properties. Topics include: - Development of innovative processing strategies to extract, modify, and recover food compounds. - Effects of industrial processes on the functionality and biological activities of food compounds. - Bioconversion of agricultural waste streams and food byproducts into added valuable compounds. - Challenges associated with processing scale-up.